Trend of Fish and Fish Seed Production in Rajasthan, India - V.K. Ujjania; N.C. Ujjania (Archives of Current Research International, 2025)
The present study attempted to elucidate the trends in fish and fish seed production of the Rajasthan state. In order for the study to evaluate the trends of fish and fish seed production, the secondary data for the period of 25 years (1999 to 2023) was collected from various sources and statistical analysis including linear, quadratic and exponential functional forms were applied. The high value of correlation coefficient (R2) in linear equations depicts a positive and significant relationship of variables i.e. time vs production of fish and fish seed. The findings on CGR (8.122 and 7.203%), CV (59.643 and 58.997), Instability indices (43.755 and 247.125) and t-test (8.361 and 8.474) depicted the variability, riskiness and instability in the fish production and fish seed production of the state. The results on trends in fish production and fish seed production would be helpful to scientists and policy makers to develop the strategy for the advanced farming management in the aquatic resources that certainly helps to enhance the fish production and fish seed production in the state of Rajasthan.